Sulfonic polyamide coating slurry and preparation method thereof, diaphragm and lithium battery

The preparation of sulfonic acid polyamide coating slurry addresses the molecular weight reduction issue in conventional treatments, enhancing the mechanical and electrochemical properties of lithium battery diaphragms, thereby improving battery performance.

CN119181929AInactive Publication Date: 2024-12-24ANHUI LIKE NEW MATERIAL TECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411691576.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2024-12-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Conventional sulfonation treatment of polyamide coating slurry for lithium battery diaphragms leads to a decrease in molecular weight, resulting in poor performance of the coating slurry layer and the diaphragm.

Method used

A method for preparing sulfonic acid polyamide coating slurry by mixing a diamine monomer with an acid chloride and a sulfonating agent in specific solvents, followed by neutralization and mixing with ceramic particles to form a slurry with improved mechanical and electrochemical properties.

Benefits of technology

The sulfonic acid polyamide coating slurry enhances the mechanical strength, wettability, and lithium ion permeability of the diaphragm, improving the electrochemical performance and energy density of lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses sulfonic polyamide coating slurry and a preparation method thereof, a diaphragm and a lithium battery, and belongs to the technical field of lithium batteries, the preparation method of the slurry comprises the following steps: (1) preparing a diamine solution; (2) preparing a polyamide solution; (3) preparing sulfonic polyamide; (4) preparing sulfonic polyamide coating slurry; the prepared sulfo polyamide coating slurry can be dissolved with water, belongs to sulfo polyamide coating water-based slurry, can avoid intervention of traditional organic solvents, and is more environmentally friendly. The prepared sulfonic polyamide coating slurry is applied to a lithium battery diaphragm, and the obtained diaphragm is high in mechanical strength, high in wettability to electrolyte and high in lithium ion penetrability. The prepared diaphragm is high in mechanical performance and high in wettability to electrolyte, and meanwhile, the transference number of lithium ions is increased, so that the electrochemical performance of a lithium battery can be improved, and the energy density and the cycling stability of the battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium batteries, and specifically relates to a sulfonic acid polyamide coating slurry and a preparation method thereof, a diaphragm and a lithium battery. Background Art

[0002] With the development of new energy vehicles, the performance requirements for lithium-ion batteries are getting higher and higher. In lithium batteries, the performance of the diaphragm is an important component of lithium batteries, and its performance is directly related to the performance of lithium batteries. Therefore, more and more research is being conducted on lithium battery diaphragms, with the aim of improving the various properties of the diaphragms, ensuring the safety of lithium batteries, and making the diaphragms play an increasingly important role in lithium batteries.

[0003] In existing diaphragms, the slurry is usually coated on the base film, which mainly includes PP base film and PE base film, and the slurry mainly includes ceramic and petroleum-based aramid. The hydrophilicity of polyamide coating slurry is poor, and sulfonation treatment is required to improve the coating slurry layer, but conventional sulfonation treatment will cause the molecular weight to decrease, resulting in poor performance of the coating slurry layer, resulting in poor performance of the diaphragm.

[0004] Therefore, the existing diaphragm coating slurry needs to be improved. Summary of the invention

[0005] The object of the present invention is to provide a sulfonic acid polyamide coating slurry and a preparation method thereof, a diaphragm and a lithium battery, so as to solve the problem of molecular weight reduction during the processing of the sulfonic acid polyamide coating slurry. The sulfonic acid polyamide coating slurry prepared by the present invention is used to prepare a diaphragm, which is beneficial to improving the mechanical properties of the diaphragm and the electrochemical properties such as the energy density of the lithium battery.

[0006] The purpose of the present invention can be achieved through the following technical solutions: In a first aspect, the present application provides a method for preparing a sulfonic acid polyamide coating slurry, comprising the following steps: (1) mixing a diamine monomer with a first solvent under an inert atmosphere to obtain a diamine solution; (2) mixing the diamine solution with an acid chloride at a temperature of 10 to 35° C. to obtain a polyamide solution; (3) mixing the polyamide solution, the sulfonating agent and a second solvent to react to obtain a sulfonic acid polyamide; the second solvent is at least one of cyclopentane sulfone and dimethyl sulfone; (4) The sulfonic acid polyamide is neutralized with alkali to adjust the pH to 6-8, and then mixed with ceramic particles and water to obtain a sulfonic acid polyamide coating slurry.

[0007] In some embodiments of the present invention, the diamine monomer is at least one of p-phenylenediamine, m-phenylenediamine, m-phenylenediamine, 4,4′-diaminodiphenyl ether and 1,2-ethylenediamine.

[0008] The first solvent is at least one of N,N-dimethylacetamide, N-methylpyrrolidone, acetone and 1,5-dimethyl-2-pyrrolidone.

[0009] The acyl chloride is at least one of terephthaloyl chloride, isophthaloyl chloride and furan dicarboxylic acid chloride.

[0010] The sulfonating agent is at least one of chlorosulfonic acid, concentrated sulfuric acid, sulfur trioxide and fuming sulfuric acid.

[0011] The ceramic particles are at least one of aluminum oxide, silicon dioxide and magnesium hydroxide.

[0012] In some embodiments of the present invention, in step (1), the mass ratio of the diamine monomer to the first solvent is 1:(4-10).

[0013] In some embodiments of the present invention, the molar ratio of the acyl chloride to the diamine monomer is (1-1.2):1.

[0014] In some embodiments of the present invention, in step (3), the mass ratio of the polyamide solution to the sulfonating agent is 1:(0.5-3), and the mass ratio of the sulfonating agent to the second solvent is (0.1-0.6):1.

[0015] In some embodiments of the present invention, in step (3), the temperature of the mixed reaction is 30-150° C., and the time is 1-12 hours.

[0016] In some embodiments of the present invention, in step (4), the mass ratio of the ceramic particles to the first solvent is (1-4):20.

[0017] In some embodiments of the present invention, the base includes at least one of lithium carbonate, lithium hydroxide, sodium carbonate, sodium bicarbonate, sodium hydroxide, calcium hydroxide, potassium hydroxide and potassium carbonate. It should be noted that the base has alkalinity and is not limited to the types listed above. Specifically, lithium salts such as lithium carbonate and lithium hydroxide are preferred, because lithium salts are not only alkaline and play a neutralizing role, but also do not affect the transmission of lithium ions, thereby improving the lithium ion transmission performance of the diaphragm.

[0018] In a second aspect, the present application proposes a sulfonic acid polyamide coating slurry prepared by the above-mentioned preparation method; the viscosity of the sulfonic acid polyamide coating slurry is 300~1500cp.

[0019] In a third aspect, the present application provides a diaphragm, comprising the above-mentioned sulfonic acid polyamide coating slurry. The diaphragm comprises: a base film and a coating slurry layer, wherein the coating slurry layer is formed by coating the above-mentioned sulfonic acid polyamide slurry on the base film.

[0020] In a fourth aspect, the present application proposes a lithium battery comprising the above-mentioned separator.

[0021] Beneficial effects of the present invention: The present invention provides a method for preparing sulfonic acid polyamide slurry, wherein a polyamide solution is first prepared, and then the obtained polyamide solution is mixed with a sulfonating agent and a second solvent, wherein the second solvent contains a sulfonyl group (-SO2-), which has almost no effect on the sulfonation reaction, and the polyamide solution and the sulfonating agent are subjected to a sulfonation reaction in a solvent containing a sulfonyl group, thereby avoiding the addition of a sulfonating agent during the polymerization reaction to reduce the molecular weight of the obtained polyamide, and since the sulfonated polyamide contains a sulfonic acid group, its affinity for water is increased, and it is easier to prepare an aqueous slurry later. Then, the sulfonic acid polyamide is neutralized with an alkali to adjust the pH, and then mixed with ceramic particles and water to obtain a sulfonic acid polyamide coating slurry.

[0022] The sulfonic acid polyamide coating slurry prepared by the present invention can be dissolved with water, and belongs to the sulfonic acid polyamide coating aqueous slurry, which can avoid the intervention of traditional organic solvents and is more environmentally friendly. The prepared sulfonic acid polyamide coating slurry is applied to the lithium battery diaphragm, and the obtained diaphragm has high mechanical strength, high wettability to the electrolyte, and strong lithium ion permeability. The diaphragm prepared by the present invention has high mechanical properties, strong wettability to the electrolyte, and at the same time improves the migration number of lithium ions, thereby improving the electrochemical performance of the lithium battery, and improving the energy density and cycle stability of the battery. DETAILED DESCRIPTION

[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] Example 1

[0025] Prepare polyamide solution: (1) Under a nitrogen atmosphere, 15 g of p-phenylenediamine and 100 g of N,N-dimethylacetamide were mixed to obtain a p-phenylenediamine solution; (2) The obtained p-phenylenediamine solution was mixed with 27 g of furan dicarboxylic acid chloride at 15°C to obtain a polyamide solution.

[0026] Preparation of sulfonic acid polyamide slurry: (1) 10 g of polyamide solution was mixed with 100 g of cyclopentane sulfone and heated to 60 °C, dissolved for 0.5 h, then 24 g of chlorosulfonic acid was added dropwise, heated to 100 °C, stirred and reacted for 4 h, then the obtained solution was poured into water, filtered to obtain a solid, and the solid was repeatedly washed with deionized water to remove the solvent, and then dried at 100 °C to obtain a sulfonic acid polyamide (Mw: 196000).

[0027] (2) The sulfonic acid polyamide was mixed with calcium hydroxide and the pH was adjusted to 7. Then, the mixture was mixed with 20 g of aluminum oxide and the viscosity was adjusted to 350 cp with water to obtain a sulfonic acid polyamide coating slurry.

[0028] Preparation of lithium battery separator: The coating liquid was coated on a polyethylene base film with a coating thickness of 4 μm, and dried at 100° C. to obtain a separator.

[0029] Preparation of lithium battery: A button cell was prepared using the above separator.

[0030] Example 2

[0031] The difference between this embodiment and embodiment 1 is that the preparation process of the polyamide solution is different: Preparation of polyamide solution: replace p-phenylenediamine with m-phenylenediamine, replace furan dicarboxylic acid chloride with terephthaloyl chloride, and the rest of the process is the same as in Example 1.

[0032] Preparation of sulfonic acid polyamide slurry: During the preparation process, calcium hydroxide was replaced with lithium carbonate, and the rest of the process was the same as in Example 1.

[0033] Preparation of lithium battery separator: The preparation process is the same as that in Example 1, wherein the sulfonic acid polyamide (Mw is 213000) is obtained.

[0034] Preparation of lithium battery: The preparation process is the same as Example 1.

[0035] Example 3

[0036] The difference between this embodiment and embodiment 1 is that the preparation process of the polyamide solution is different: Preparation of polyamide solution: Replace furan dicarboxylic acid chloride with isophthaloyl chloride, and the rest of the process is the same as in Example 1.

[0037] Preparation of sulfonic acid polyamide slurry: During the preparation process, calcium hydroxide was replaced by lithium hydroxide, and the rest of the process was the same as in Example 1.

[0038] Preparation of lithium battery separator: The preparation process is the same as that in Example 1, wherein the obtained sulfonic acid polyamide (Mw is 204000) is obtained.

[0039] Preparation of lithium battery: The preparation process is the same as Example 1.

[0040] Example 4

[0041] The difference between this embodiment and embodiment 1 is that the preparation process of the sulfonic acid polyamide in the sulfonic acid polyamide slurry is different: Preparation of polyamide solution: The preparation process is the same as Example 1.

[0042] Preparation of sulfonic acid polyamide slurry: 100 g of sulfolane was replaced by 100 g of dimethyl sulfone, and the rest was the same as in Example 1. The obtained sulfonic acid polyamide (Mw: 187,000) was obtained.

[0043] Preparation of lithium battery separator: The preparation process is the same as Example 1.

[0044] Preparation of lithium battery: The preparation process is the same as Example 1.

[0045] Example 5

[0046] The difference between this embodiment and embodiment 1 is that the preparation process of the sulfonic acid polyamide in the sulfonic acid polyamide slurry is different: Preparation of polyamide solution: The preparation process is the same as Example 1.

[0047] Preparation of sulfonic acid polyamide slurry: 24 g of chlorosulfonic acid was replaced by 24 g of concentrated sulfuric acid, and the rest was the same as in Example 1. The obtained sulfonic acid polyamide (Mw: 228,000) was obtained.

[0048] Preparation of lithium battery separator: The preparation process is the same as Example 1.

[0049] Preparation of lithium battery: The preparation process is the same as Example 1.

[0050] Example 6

[0051] The difference between this embodiment and embodiment 1 is that the preparation process of the sulfonic acid polyamide slurry is different: Preparation of polyamide solution: The preparation process is the same as Example 1.

[0052] Preparation of sulfonic acid polyamide slurry: 10g polyamide solution was mixed with 100g cyclobutane sulfone, dissolved for 0.5h, 12g chlorosulfonic acid was added dropwise, heated to 80°C, stirred for 1h, the reaction solution was poured into water and stirred vigorously, filtered to obtain solid, and the solid was repeatedly washed with deionized water to remove the solvent, and dried at 80~120°C to obtain sulfonic acid polyamide. Among them, the obtained sulfonic acid polyamide (Mw is 173000). The above sulfonic acid polyamide was mixed with calcium hydroxide, the pH was adjusted to 7, and then mixed with 20g silica, and the viscosity was adjusted to 1200cp with water to obtain sulfonic acid polyamide coating slurry.

[0053] Preparation of lithium battery separator: The preparation process is the same as Example 1.

[0054] Preparation of lithium battery: The preparation process is the same as Example 1.

[0055] Example 7

[0056] The difference between this embodiment and embodiment 1 is that the preparation process of the sulfonic acid polyamide slurry is different: Preparation of sulfonic acid polyamide slurry: 10g polyamide solution was mixed with 50g cyclobutane sulfone and 50g dimethyl sulfone, heated to 120°C, dissolved for 0.5h, 12g chlorosulfonic acid was added dropwise, stirred for 2h, the reaction solution was poured into hot water and stirred vigorously, filtered to obtain solid, and the solid was repeatedly washed with deionized water to remove the solvent, and dried at 80-120°C to obtain sulfonic acid polyamide, wherein the obtained sulfonic acid polyamide (Mw is 167000). The sulfonic acid polyamide was mixed with calcium hydroxide, the pH was adjusted to 7, and then mixed with 20g silica, and the viscosity was adjusted to 1200cp with water to obtain sulfonic acid polyamide coating slurry.

[0057] Preparation of lithium battery separator: The preparation process is the same as Example 1.

[0058] Preparation of lithium battery: The preparation process is the same as Example 1.

[0059] Comparative Example 1 Compared with Example 1, this comparative example does not undergo sulfonation treatment: Prepare polyamide solution: (1) Under a nitrogen atmosphere, 15 g of p-phenylenediamine and 100 g of N,N-dimethylacetamide were mixed to obtain a p-phenylenediamine solution; (2) The obtained p-phenylenediamine solution was mixed with 27 g of furan dicarboxylic acid chloride at 15°C to obtain a polyamide solution.

[0060] Preparation of polyamide slurry: The obtained polyamide solution was mixed with calcium hydroxide, the pH was adjusted to 7, and then mixed with 20 g of aluminum oxide, and the viscosity was adjusted to 400 cp with water to obtain polyamide coating slurry.

[0061] Preparation of lithium battery separator: The preparation process is the same as Example 1.

[0062] Preparation of lithium battery: The preparation process is the same as Example 1.

[0063] Comparative Example 2 The difference between this comparative example and Example 1 is that the preparation process of the sulfonic acid polyamide in the sulfonic acid polyamide slurry is different: Preparation of polyamide solution: The preparation process is the same as Example 1.

[0064] Preparation of sulfonic acid polyamide slurry: (1) 10 g of polyamide solution was mixed with 100 g of DMSO (dimethyl sulfoxide), heated to 60 °C, and dissolved for 0.5 h. Then, 24 g of chlorosulfonic acid was added dropwise, heated to 100 °C, and stirred for reaction for 4 h to obtain sulfonic acid polyamide (Mw: 98,000). The solution was then poured into water, filtered to obtain a solid, and the solid was repeatedly washed with deionized water to remove the solvent therein, and then dried at 100 °C to obtain sulfonic acid polyamide.

[0065] (2) Sulfonic acid polyamide and calcium hydroxide were mixed, the pH was adjusted to 7, and then 20 g of aluminum oxide was added. The viscosity was adjusted to 350 cp with water to obtain a sulfonic acid polyamide coating slurry.

[0066] Preparation of lithium battery separator: The preparation process is the same as Example 1.

[0067] Preparation of lithium battery: The preparation process is the same as Example 1.

[0068] Comparative Example 3 The difference between this comparative example and Example 1 is that the preparation process of the sulfonic acid polyamide in the sulfonic acid polyamide slurry is different: Preparation of polyamide solution: The preparation process is the same as Example 1.

[0069] Preparation of sulfonic acid polyamide slurry: (1) 10 g of polyamide solution was mixed with 100 g of NMP (N-methylpyrrolidone), heated to 60 °C, and dissolved for 0.5 h. Then, 24 g of chlorosulfonic acid was added dropwise, heated to 100 °C, and stirred for reaction for 4 h to obtain sulfonic acid polyamide (Mw: 89000). The solution was then poured into water, filtered to obtain a solid, and the solid was repeatedly washed with deionized water to remove the solvent therein, and then dried at 100 °C to obtain sulfonic acid polyamide.

[0070] (2) Sulfonic acid polyamide was mixed with calcium hydroxide, the pH was adjusted to 7, and then mixed with 20 g of aluminum oxide, and the viscosity was adjusted to 350 cp with water to obtain a sulfonic acid polyamide coating slurry.

[0071] Preparation of lithium battery separator: The preparation process is the same as Example 1.

[0072] Preparation of lithium battery: The preparation process is the same as Example 1.

[0073] The performance of the lithium battery separators obtained in Examples 1 to 7 and Comparative Examples 1 to 3 was tested, and the lithium batteries obtained in Examples 1 to 7 and Comparative Examples 1 to 3 were tested for electrochemical impedance. The test results are shown in Table 1.

[0074] Table 1

[0075] It can be seen from Table 1 that, based on the data of the diaphragms prepared in Examples 1-7, the diaphragms prepared by the present technical solution have high mechanical properties and strong wettability to the electrolyte, while also improving the migration number of lithium ions, thereby improving the electrochemical performance of lithium batteries and improving the energy density and cycle stability of batteries.

[0076] In Comparative Example 1, the polyamide was not sulfonated, and was coated on the separator after being made into slurry. The hydrophilicity of the battery separator was poor, which was manifested by a significantly larger contact angle. The lithium ion migration number was significantly smaller, which was not conducive to improving the electrochemical performance of the lithium battery, such as the energy density.

[0077] In Comparative Examples 2 and 3, after the solvent is replaced with DMSO or NMP, the molecular weight of the sulfonic acid polyamide obtained after the sulfonation reaction is significantly reduced, which is not conducive to the subsequent improvement of the mechanical properties of the diaphragm.

[0078] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0079] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a sulfonic acid polyamide coating slurry, characterized in that: The steps include: (1) mixing a diamine monomer with a first solvent under an inert atmosphere to obtain a diamine solution; (2) mixing the diamine solution with an acid chloride at a temperature of 10 to 35° C. to obtain a polyamide solution; (3) mixing the polyamide solution, the sulfonating agent and a second solvent to react to obtain a sulfonic acid polyamide; the second solvent is at least one of cyclopentane sulfone and dimethyl sulfone; (4) The sulfonic acid polyamide is neutralized with alkali to adjust the pH to 6-8, and then mixed with ceramic particles and water to obtain a sulfonic acid polyamide coating slurry.

2. The method for preparing a sulfonic acid polyamide coating slurry according to claim 1, characterized in that: The diamine monomer is at least one of p-phenylenediamine, m-phenylenediamine, m-phenylenediamine, 4,4′-diaminodiphenyl ether and 1,2-ethylenediamine; The first solvent is at least one of N,N-dimethylacetamide, N-methylpyrrolidone, acetone and 1,5-dimethyl-2-pyrrolidone; The acyl chloride is at least one of terephthaloyl chloride, isophthaloyl chloride and furan dicarboxylic acid chloride; The sulfonating agent is at least one of chlorosulfonic acid, concentrated sulfuric acid, sulfur trioxide and fuming sulfuric acid; The ceramic particles are at least one of aluminum oxide, silicon dioxide and magnesium hydroxide.

3. The method for preparing a sulfonic acid polyamide coating slurry according to claim 1, characterized in that: In step (1), the mass ratio of the diamine monomer to the first solvent is 1:(4-10).

4. The method for preparing a sulfonic acid polyamide coating slurry according to claim 1, characterized in that: The molar ratio of the acyl chloride to the diamine monomer is (1-1.2):

1.

5. The method for preparing a sulfonic acid polyamide coating slurry according to claim 1, characterized in that: In step (3), the mass ratio of the polyamide solution to the sulfonating agent is 1:(0.5-3), and the mass ratio of the sulfonating agent to the second solvent is (0.1-0.6):

1.

6. The method for preparing a sulfonic acid polyamide coating slurry according to claim 1, characterized in that: In step (3), the temperature of the mixed reaction is 30-150° C. and the time is 1-12 hours.

7. The method for preparing a sulfonic acid polyamide coating slurry according to claim 1, characterized in that: In step (4), the mass ratio of the ceramic particles to the first solvent is (1-4):20; The base includes at least one of lithium carbonate, lithium hydroxide, sodium carbonate, sodium bicarbonate, sodium hydroxide, calcium hydroxide, potassium hydroxide and potassium carbonate.

8. A sulfonic acid polyamide coating slurry, characterized in that: Prepared by the preparation method described in any one of claims 1-7; the viscosity of the sulfonic acid polyamide coating slurry is 300~1500cp.

9. A diaphragm, characterized in that: The invention comprises a base film and a coating slurry layer, wherein the coating slurry layer is formed by coating the sulfonic acid polyamide coating slurry prepared by the method described in any one of claims 1 to 7 or by coating the sulfonic acid polyamide slurry described in claim 8 on the base film.

10. A lithium battery, characterized in that: The diaphragm according to claim 9 is included.

Citation Information

Patent Citations

  • Method for manufacturing sulfonated aromatic polymer

    CN103998492A

  • Preparation method of furyl polyamide with high heat resistance and application of furyl polyamide in lithium ion battery

    CN116554465A

  • Preparation method of sulfonic polyamide

    CN118546357A

  • Water-based coating slurry, lithium battery diaphragm and preparation method of lithium battery diaphragm

    CN118867566A

  • Method of making sulfonic group-containing aromatic compound

    WO2013040768A1